FRI0177 Analysis of Effectiveness, Safety and Cost of Different Doses of Rituximab in a Cohort of Patients with Rheumatoid Arthritis. (9th June 2015) - Mena-Vazquez, N.; Manrique-Arija, S.; Ordoñez-Cañizares, M.C.; Domic, C.; Ureña-Garnica, I.; Romero Barco, C.M.; Jiménez-Núñez, F.G.; Rojas-Giménez, M.; Fuego, C.; Cano-García, L.; Irigoyen-Oyarzábal, M.V.; Coret, V.; et al.
Abstract : Objectives: To evaluate the effectiveness, cost and safety of Rituximab (RTX) in patients with rheumatoid arthritis (RA) depending on the dose used. Methods: Design: Observational, retrospective study. Patients: Patients with RA treated with at least one dose of RTX and followed in the department of Rheumatology, Hospital de Malaga, were included. According to the doses used, 3 groups were obtained: (1): First and following courses consisting of 2 infusions of 1g, 15 days apart; (2): First course of 2 infusions of 1g followed by courses of 2 infusions of 500mg, 15 days apart; and (3): First course and following courses consistent on 2 infusions of 500mg, 15 days apart. Courses were repeated "on demand", according to clinical presentation. Outcome variables: Primary: Effectiveness of treatment between groups. Secondary: cost and incidence rate of adverse effects (AE). Protocol and description of variables: RA patients who had received at least one infusion with RTX from 2007-2012 were included. The number of courses adjusted to treatment time (patient-years) were analyzed, the direct costs were defined as the cost of treatment with RTX per group and were compared with the theoretical costs of systematic semiannual courses. AE rates by type and severity stratified by treatment group. Statistical analysis: the primary endpoint of effectiveness, duration of treatment with RTX, was analyzed using Kaplan Meier and the comparation between groups was made with the Log Rank. Incidence rates of AE was performed. Results: 52 patients were included. The groups showed only differences in sex ratio and order of RTX was used compared to other biologic therapies. The cohort was followed for 135.34 patient-years. Group 2 was the one with longer time in treatment with RTX. Group 1 required less adjusted to time courses. Group 2 was the most expensive with a median cost per patient of € 484.89 per month. The savings per patient per year in group 3 compared with group 2 was 556.48€ and in group 1 compared to group 2 was 137.28€. The biggest saving occurred with the administration of courses "on demand" respect "systematic" (479.32€ versus 799.74€). No differences were found in the incidence of total AE (group 1 =33%, group 2 =35%, group 3 =33%). When only considered severe, the incidence rate (IR) was higher in group 1 (11%) compared to the other 2 (group 2 =3% and group 3 =0%; p=0, 05). The IR of serious infections was higher in group 1. Conclusions: The administration of a full dose course followed by reduced dose courses seems slightly more expensive but the most effective option. Patients treated from the start with full dose courses, needed fewer courses/patient-year. Dose reducted courses from full dose courses do not produce huge savings compared to money spare achieved by the administration "on demand". The rate of AE may be greater in patients treated with full doses of RTX compared with those treated with low doses, although these differences might be biased, in part, by the greater proportion of first line biologic treated patients of group 1. The IR of serious infections was similar to the expected in a first biological treatment option. Disclosure of Interest: None declared